IT support to management control in small and medium-sized enterprises - Dyczkowska, Joanna; Dyczkowski, Tomasz (Research Papers of Wrocław University of Economics, 2018)
IT systems are seen as invaluable support to financial and accounting specialists, however, many enterprises are unable to use their analytical potential. The paper validates a positive contribution of the systems to the effectiveness of management control in small and medium-sized companies. The research included 129 Polish SMEs. Even though IT systems of ERP and BI classes were not commonly available (they were used by 18.6% of SMEs), it was observed that financial and management accounting received adequate IT support (in 58.1% of cases). Furthermore, sales and customer service were seen as domains were ITS contributed the most to the business. Finally of 51 SMEs which had no access to advanced software, only 7 found that situation negative
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515, s. 13-25
Keywords: control; information systems; planning; small and medium-sized companies; kontrola; systemy informatyczne; planowanie; małe i średnie przedsiębiorstwa